Virtual Communication Patterns of Mobile Legends Gamers' Journalism in Youth Sarcasm Actions in Kisaran City, Asahan Regency - Riani Iskandar Batubara, Gadis; Saragih, M. Yoserizal (Jurnal Spektrum Komunikasi, 2024)
Game journalism is a field of journalism that focuses on the gaming industry and gaming culture. Online gaming journalism is the process of reporting and making news about the online gaming industry and esports content. Mobile Legend is one of the MOBA games available for mobile play. Ten players in two teams typically play these games, following a five-versus-five format. In Mobile Legends, users have the ability to communicate through the virtual world. The process of virtual communication involves conveying messages to others within the virtual environment. This study aims to determine how the virtual communication patterns used by mobile gamers influence the sarcasm of the Asahan district's remains. The results of this study show that mobile Legends gamers in the district are more likely to use the voice chat and manual chat features as a virtual communication tool to convey the circus words or sentences that players use in mobile Legends online games. Then, gamers employ circular communication patterns, which involve a message delivery process that allows both communicators to exchange functions. As is the case with a player who starts commenting on a bad game from another player, that comment is given feedback against the commentator and can be replied to by the team member to give another feedback. This study employs qualitative research methods such as library study, observation and interview techniques, virtual ethnography methods, and documentation as an additional method.